Expression of luteinizing hormone receptor during development of bovine fetal ovary - Giroto, Alan Brunholi; Chaves, Marina Platzeck; dos Santos, Priscila Helena [UNESP]; Fontes, Patrícia Kubo [UNESP]; Nunes, Sarah Gomes [UNESP]; Manssur, Thainá Sallum Bacco; Mendes, Leonardo Oliveira; de Souza Castilho, Anthony César (FapUNIFESP (SciELO), 2024)
Steroids and gonadotrophins are essential for the regulation of late stages of preantral development and antral follicular development. Although the luteinizing hormone receptor (LHCGR) has been detected in the preantral follicles of rats, rabbits, and pigs, its expression, in bovine fetal ovary, has not been demonstrated. Based on this, we aimed to investigate the expression of the LHCGR and LHCGR mRNA binding protein (LRBP), as well as, to quantify bta-miR-222 (a regulatory microRNA of the LHCGR gene) during the development of bovine fetal ovary. In summary, LHCGR expression was observed in the preantral follicle in bovine fetal ovary, from oogonias to primordial, primary and secondary stages, and the mRNA abundance was lower on day 150 than day 60. However, the mRNA abundance of LRBP followed the opposite pattern. Similar to LRBP, the abundance of bta-miR-222 was higher on day 150 than day 60 or 90 of gestation. The LHCGR protein was detected in oogonia, primordial, primary, and secondary follicles. Moreover, both oocytes and granulosa cells showed positive immunostaining for LHCGR. In conclusion, we suggest the involvement of LHCGRLRBPbta-mir222 with mechanisms related to the development of preantral follicles in cattle.
Keywords: LHCGR; microRNAs; preantral follicle; steroidogenesis